Gonadal Dysfunction in Wolfram Syndrome: A Prospective Study - Gema Esteban-Bueno; Juan Luis Fernández-Martínez (Diagnostics, 2025)
Background: Wolfram syndrome (WFS), also known as DIDMOAD, is a rare monogenic neurodegenerative disorder characterized by four key components: non-autoimmune insulin-dependent diabetes mellitus (DM), optic atrophy, sensorineural hearing loss, and diabetes insipidus. Although it significantly affects quality of life, gonadal dysfunction, particularly hypogonadism, remains underrecognized. Methods: In total, 45 patients (25 men, 20 women) with genetically confirmed WFS from a single tertiary-care center were prospectively followed to assess gonadal function. Men underwent hormonal evaluations, semen analysis, imaging tests, and testicular biopsies. In women, data on age at menarche, menstrual irregularities, and age at menopause were recorded. Hormonal analyses, including anti-Müllerian hormone (AMH) levels, and imaging tests were also conducted. Results: Hypogonadism was identified in 19 men (76.0%), of whom 17 (68.0%) had hypergonadotropic hypogonadism and 2 (8.0%) had hypogonadotropic hypogonadism. Testicular biopsies showed seminiferous tubule damage, Sertoli cell predominance, and reduced Leydig cells. Azoospermia was observed in 12 patients, whereas others presented with oligozoospermia, teratozoospermia, or asthenozoospermia. Most patients exhibited low testosterone levels along with elevated LH and FSH, suggesting primary testicular failure, except for two cases of hypogonadotropic hypogonadism. Correlations between biomarkers, onset age and severity have been analyzed and provide important insights regarding medical treatment. In women, menstrual irregularities were universal, with 20% experiencing premature menopause. Four patients had low AMH levels, with ovarian atrophy in three and a postmenopausal uterus in two, indicating early hypogonadism risk. Conclusions: Gonadal dysfunction is a significant yet overlooked feature of WFS, requiring systematic evaluation during puberty and beyond. Proper management is essential to mitigate metabolic disturbances and psychological impacts, including infertility distress, relationship challenges, and quality of life concerns. Addressing sexual health is crucial as WFS patients live longer and aspire to establish relationships or start families.